Ocean Biogeochemical Signatures of the North Pacific Blob. Issue 9 (7th May 2022) - Mogen, Samuel C.; Lovenduski, Nicole S.; Dallmann, Allysa R.; Gregor, Luke; Sutton, Adrienne J.; Bograd, Steven J.; Quiros, Nathali Cordero; Di Lorenzo, Emanuele; Hazen, Elliott L.; Jacox, Michael G.; Buil, Mercedes Pozo; Yeager, Stephen
Abstract: The Blob was the early manifestation of the Northeast Pacific marine heat wave from 2013 to 2016. While the upper ocean temperature in the Blob has been well described, the impacts on marine biogeochemistry have not been fully studied. Here, we characterize and develop understanding of Eastern North Pacific upper ocean biogeochemical properties during the Winter of 2013–2014 using in situ observations, an observation‐based product, and reconstructions from a collection of ocean models. We find that the Blob is associated with significant upper ocean biogeochemical anomalies: A 5% increase in aragonite saturation state (temporary reprieve of ocean acidification) and a 3% decrease in oxygen concentration (enhanced deoxygenation). Anomalous advection and mixing drive the aragonite saturation anomaly, while anomalous heating and air‐sea gas exchange drive the oxygen anomaly. Marine heatwaves do not necessarily serve as an analog for future change as they may enhance or mitigate long‐term trends. Plain Language Summary: The global ocean is experiencing major changes due to human‐made carbon emissions and climate change, leading to a warming ocean with increasing acidity and declining oxygen. On top of these long‐term changes in the ocean are short‐term extreme events, such as marine heatwaves. These extreme events quickly change the ocean state and can stress marine ecosystems in multiple ways. The Northeast Pacific marine heat wave (2013–2016) was one such marine heatwave. Here we focus on the early portion of this marine heatwave, called the Blob. While the ocean temperature changes during the event are well understood, the effects on ocean biogeochemistry have not been fully examined. In this study, we use an earth system model that accurately simulates the Blob to examine short‐term changes in oxygen and acidity. We find that the warming signal leads to a decline in the effects of ocean acidification, mainly due to changes in the movement of carbon, and lowers the amount of oxygen, due primarily to temperature‐driven effects. These results suggest that some effects of climate change may be exacerbated (warming) or mitigated (ocean acidification) by marine heatwaves. Key Points: The North Pacific Blob had a distinct biogeochemical signature that is captured by observations and multiple ocean models The Blob was characterized by anomalously high aragonite saturation states and anomalously low oxygen concentrations The biogeochemical signature of the Blob was driven by changes in temperature and physical ocean circulation processes